Pendekatan Modeling Games Untuk Meningkatkan Kemampuan Dribbling Sepakbola Usia 10-13 Tahun - Sitompul, Surya Rezeki; Perada, Ready Aqsa (Jurnal Speed (Sport, Physical Education, Empowerment), 2024)
This study aims to address dribbling weaknesses with a game-based training approach, exercises that are arranged based on the characteristics of student skills by considering the training patterns that prioritize games, the results of pre-tests with dribbling skill tests with dribbling skill tests on dribbling skill in Sulcata soccer school students aged 10-13 years. The method used in this study used an experimental approach, this experimental research used a pre-experimental design, which is a research design that uses a group or class with the implementation of pre-test and post-test. The sample of Sulcata soccer students aged 10-13 used by the researchers includes a total of 24 subjects. From the results of the t-test, it can be seen that the t-number is 11.019> 2.069 (t-table) and the probability value is 0.000 <0.05, then Ho is rejected and Ha is accepted, which means that there is a significant effect of training games on dribbling ability in soccer students aged 10-13 years old in Sulcata, considering the pre-test average of 18.39 and the post-test average of 17.32, there is a mean difference of 1.07, which shows that training games on dribbling ability in students have a 6.3% better change than before. Keywords: Dribbling, Games, Soccer, Modeling.